A Sustainable and Efficient Synthesis of Benzyl Phosphonates Using PEG/KI Catalytic System - Gawande, Manoj B.; Disale, Shamrao; Kale, Sandip; Abraham, George; Kahandal, Sandeep; Sawarkar, Ashish (Frontiers in Chemistry, 2016)
An efficient and expedient protocol for the synthesis of benzyl phosphonates using KI/K2CO3 as a catalytic system and PEG-400 as benign solvent has been developed. The reaction proceeds smoothly at room temperature achieving excellent selectivity and yield of the corresponding products. The combination of PEG-400, KI and K2CO3 in this reaction avoids the need of volatile/toxic organic solvents and reactive alkali metals or metal nanoparticles/hydrides. We believe that this benign combination (PEG-400 and KI) could be used for other related organic transformations.